Alleviating the Cadmium Toxicity and Growth‐Promotion in Paddy Rice by Photosynthetic Bacteria. Issue 3 (30th January 2019) - Xiao, Xian; Zhao, Yuan; Zhou, Qin; Wang, Leyang; Zhang, Xujie; Zhao, Lihua; Zhang, Sheng
Abstract : Cadmium (Cd) accumulation in rice and its subsequent transfer to food chain has become a major environmental issue worldwide. Low growth in plants and high toxicity toward the living organism are major drawbacks associated with Cd contamination. Effective immobilization and reducing Cd uptake by rice grains can be promising strategies to minimize its toxicity. Here, the authors report an effective method for Cd immobilization by inoculating photosynthetic bacteria known as Rhodopseudomonas palustris (RP) in the soils, which is verified through pot and field experiments. The pot experiment indicated that high Cd contamination in control soils inhibited plant growth and decreased the biomass massively in paddy rice. Bacterial immobilization of Cd not only inhibited its uptake by plants but also increased fresh weight of rice seedlings under low Cd concentration (40 mg kg −1 soil). However, under high Cd concentration (80 mg kg −1 ), Bacillus subtilis enhanced the activity of RP for reducing the Cd uptake and subsequent accumulation in rice grains (from 0.65 to 0.19 mg Cd kg −1 ) to below the standard limits (0.2 mg kg −1 ). Field experiments showed that Cd prefers to accumulate in the root region, and the transmission process through roots, stems, and leaves are restricted for ultimately decreasing the Cd accumulation in rice grains. In natural soil with low Cd contamination, the rice grains can be safely edible. These findings will assist to minimize the Cd toxicity in human health and to address the food safety challenges of modern world. Abstract : An effective method for Cd immobilization can be achieved by Rhodopseudomonas palustris inoculation in Cd‐contaminated soils. It is shown that in natural soil with low Cd contamination, the rice grains can be safely edible.